Pengaruh Motivasi Kerja, Praktik Kerja Industri, dan Efikasi Diri terhadap Kesiapan Kerja Siswa SMK Negeri 4 Malang - Maulanada, Afifah; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract One of the main components of economic transformation is human resources (HR). This is where vocational education becomes important in meeting the need for competent mid-level professional workers to support international competition. However, the fact is that not all vocational school graduates are able to produce professional workers. There are still many roles that vocational education institutions should play in producing competent middle-level workers. This is proven by the large number of Vocational High School (SMK) graduates who are unemployed. Work readiness factors are work motivation, industrial work practices (prakerin), and student self-efficacy according to the skills possessed by the student. The aim of this research is to determine and analyze the influence of work motivation, industrial work practices and self-efficacy. The population in this study were students of SMK Negeri 4 Malang. Determining the sample size using the Slovin formula obtained 92 respondents, and using a simple random sampling approach. Data were analyzed using multiple linear regression tests. The research results obtained were that there was a positive and significant influence between work motivation, industrial work practices, and self-efficacy on the work readiness of students at SMK Negeri 4 Malang. Keywords: Work Motivation, Industrial Work Practices, Self-Efficacy, and Readiness Work